Pemberdayaan Forum Guru Muhammadiyah (FGM) Melalui Literasi Digital QR Code Generator dengan Barcode - Suardi Suardi; Muhajir Muhajir; Indah Ainun Mutiara; Herdianty Ramlan; Thomy Sastra Atmaja (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Teacher problems that are the main concern in this community service program are (1) The lack of subject books and subject modules owned by the Muhammadiyah teacher group (2) The low knowledge and skills of teachers and students related to educational technology, especially in making QR-based digital literacy Code Generator with Barcodes. The solution to solving this problem is digital literacy training based on QR Code Generator with Barcodes for Muhammadiyah teacher groups, so that it can make it easier to have subject books and subject modules that teachers can use in learning in the new normal era through gadgets. The implementation method is carried out through four stages, namely (1) digital literacy construction, (2) digital literacy is maintained by the community, (3) improving and updating digital literacy and the resulting changes. The results of community service activities show that the Empowerment of the Muhammadiyah Teacher Forum (FGM) through digital literacy based on QR Code Generator with Barcodes is carried out by involving school principals, teachers and students starting from the socialization stage, the stage of making digital literacy designs, the stage of printing digital literacy designs, the stage of delivering material digital literacy, the stage of training the use of digital literacy, the stage of sharing digital literacy and the stage of using digital literacy QR Code Generator with Barcode. The Muhammadiyah Teacher Forum (FGM) Empowerment activity through digital literacy based on the QR Code Generator with Barcodes received a positive response from school principals, teachers and students because they considered this activity useful and very beneficial. Permasalahan guru yang menjadi perhatian utama dalam program pengabdian kepada masyarakat ini adalah (1) Minimnya buku mata pelajaran dan modul mata pelajaran yang dimiliki oleh kelompok guru muhammadiyah (2) Rendahnya pengetahuan dan keterampilan guru dan siswa terkait teknologi pendidikan terkhusus dalam membuat literasi digital berbasis QR Code Generator dengan Barcode. Solusi untuk mengatasi masalah tersebut adalah pelatihan literasi digital berbasis QR Code Generator dengan Barcode untuk kelompok guru Muhammadiyah, agar dapat memudahkan memiliki buku mata pelajaran dan modul mata pelajaran yang bisa dipakai guru dalam pembelajaran di masa new normal melalui gadget. Metode pelaksanaan dilakukan melalui empat tahap yaitu (1) konstruksi literasi digital, (2) literasi digital dipelihara oleh masyarakat, (3) memperbaiki dan memperbaharui literasi digital dan perubahan yang dihasilkan. Hasil kegiatan pengabdian kepada masyarakat menunjukkan Pemberdayaan Forum Guru Muhammadiyah (FGM) melalui Literasi digital berbasis QR Code Generator dengan Barcode dilakukan dengan melibatkan kepala sekolah, guru dan siswa mulai tahap sosialisasi, tahap membuat desain literasi digital, tahap mencetak desain literasi digital, tahap penyampaian materi literasi digital, tahap melatih penggunaan literasi digital, tahap membagikan literasi digital dan tahap menggunakan literasi digital QR Code Generator dengan Barcode. Kegiatan Pemberdayaan Forum Guru Muhammadiyah (FGM) melalui Literasi digital berbasis QR Code Generator dengan Barcode mendapatkan respons positif dari kepala sekolah, guru dan siswa karena menganggap kegiatan tersebut bermanfaat dan sangat bermanfaat.